The influence of sugar concentration and fermentation time of green tea kombucha (Camellia sinensis) on its halal and safety aspects - Falasifah, Ratu; Diyah Dewanti, Beauty Suestining; Zubaidah, Elok; Sucipto, Sucipto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Kombucha is a fermented tea beverage made from Camellia sinensis and sugar using a Symbiotic Culture of Bacteria and Yeast (SCOBY). It is known for its health benefits, including immune system support, antimicrobial activity, anti-inflammatory properties, and probiotic effects. However, its ethanol content raises concerns among the predominantly Muslim Indonesian population. This study aims to evaluate the influence of sugar concentration and fermentation time on the halal and safety aspects of green tea kombucha. A Randomized Block Design (RBD) was employed, with sugar concentrations of 5%, 7.5%, 10%, and 12.5% (w/v) and fermentation durations of 8, 10, and 12 days, resulting in 36 experimental samples. Data were analyzed using Two-Way ANOVA (α = 0.05) in IBM SPSS Statistics 26, followed by Duncan’s Multiple Range Test (DMRT) when interactions were significant. Measured parameters included pH, total acidity, and ethanol content. Results showed that fermentation time and sugar concentration significantly influenced pH (2.61–2.78), total acidity (0.055%–0.188%), and ethanol content (0.090%–0.199%). These values met halal and safety standards, with ethanol <0.5%, acidity 0.2%–0.9%, and pH 2.5–4.2. Thus, green tea kombucha is deemed safe and halal for consumption.